Pulsed cavitational therapy using high-frequency ultrasound for the treatment of deep vein thrombosis in an in vitro model of human blood clot. (21st November 2017) - Goudot, G; Mirault, T; Arnal, B; Boisson-Vidal, C; Le Bonniec, B; Gaussem, P; Galloula, A; Tanter, M; Messas, E; Pernot, M
Abstract: Post-thrombotic syndrome, a frequent complication of deep venous thrombosis, can be reduced with early vein recanalization. Pulsed cavitational therapy (PCT) using ultrasound is a recent non-invasive approach. We propose to test the efficacy and safety of high-frequency focused PCT for drug-free thrombolysis (thrombotripsy) in a realistic in vitro model of venous thrombosis. To reproduce venous thrombosis conditions, human whole blood was allowed to clot by stasis in silicone tubes (6 mm internal diameter) at a 30 cm H2 O pressure, maintained during the whole experiment. We engineered an ultrasound device composed of dual 2.25 MHz transducers centered around a 6 MHz imaging probe. A therapeutic focus was generated at a 3.2 cm depth from the probe. Thrombotripsy was performed by longitudinally scanning the thrombus at three different speeds: 1 mm s −1 ( n = 6); 2 mm s −1 ( n = 6); 3 mm s −1 ( n = 12). Restored outflow was measured every three passages. Filters were placed to evaluate the debris size. Twenty-four occlusive thrombi, of 2.5 cm mean length and 4.4 kPa mean stiffness, were studied. Flow restoration was systematically obtained by nine subsequent passages (4.5 min maximum). By varying the device's speed, we found an optimal speed of 1 mm s −1 to be efficient for effective recanalization with 90 s (three passages). Within 90 s, flow restoration was of 80, 62 and 74% at respectively 1, 2 and 3 mm s −1 . For all groups, cavitation cloud drilled a 1.7 mm mean diameter channel throughout the clot. Debris analysis showed 92% of debris <10 µ m, with no fragment > 200 µ m.